2000
DOI: 10.1016/s0378-4290(00)00076-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved methodologies for breeding striga-resistant sorghums

Abstract: Parasitic¯owering weeds of the genus Striga (Scrophulariaceae) cause substantial losses in sorghum [Sorghum bicolor (L.) Moench] production in sub-Saharan Africa. Striga-resistant sorghum cultivars could be a major component of integrated striga management, if resistance was available in adapted, productive germplasm. In this paper we review methodologies for breeding striga-resistant sorghums. The agar-gel assay is an excellent tool to screen host genotypes in the laboratory for low production of the striga s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(174 citation statements)
references
References 39 publications
5
169
0
Order By: Relevance
“…Field screening under artificial infestation is not always practical due to the fact that it can cause Striga seeds spreading to novel regions and it is moreover not consistent because breeders do not have any control of the parasite density and distribution (Haussmann et al, 2000). Pot screening has been operative as an alternative technique to confirm uniform infestation of Striga seeds.…”
Section: Pot Screeningsmentioning
confidence: 99%
“…Field screening under artificial infestation is not always practical due to the fact that it can cause Striga seeds spreading to novel regions and it is moreover not consistent because breeders do not have any control of the parasite density and distribution (Haussmann et al, 2000). Pot screening has been operative as an alternative technique to confirm uniform infestation of Striga seeds.…”
Section: Pot Screeningsmentioning
confidence: 99%
“…In sorghum, several cultivars and breeding lines have been reported to be resistant and/or tolerant to Striga Rodenburg et al 2006;Ejeta, 2007). Most of these donor sources have been summarized in Haussmann et al (2000) and include Dobbs, Framida (SRN 4841), 555, N 13, SRN 6496, and SRN 39 (Ramaiah, 1987;Ezeaku and Gupta, 2004). Tesso et al (2007) reported three sorghum cultivars (P-9401, P-9403 and PSL85061) to express resistance to Striga.…”
Section: Sources Of Resistancementioning
confidence: 99%
“…Relatively few cultivars with good level of Striga resistance have been identified in millet crops, mainly sorghum and pearl millet Kountche et al, 2013). Improved breeding approaches that promise good prospects for developing cultivars with resistance to Striga have been suggested to take advantage of the ever-growing knowledge of the complex nature of the host-parasite interactions Haussmann et al, 2000;Omanya et al 2004). Adoption of these strategies has resulted in the development of appropriate breeding populations, and deployment of deliberate selection for resistance to Striga.…”
Section: Conventional Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The following observations were made in the two central rows of each plot (10 hills, or a total area of 1.92 m²): (1) symptoms of fungal disease on sorghum, (2) weekly counts of emerged Striga plants from four to twelve weeks after the first emergence of Striga in the experiment, (3) visual estimation of vigour of emerged Striga plants (Haussmann et al, 2000) at 85 DAS, (4) weight of Striga dry biomass at sorghum harvest and (5) sorghum yield. Striga count data were used to calculate area under the Striga number progress curve (ASNPC, Haussmann et al, 2000).…”
Section: Data Collection and Analysismentioning
confidence: 99%